Type of Bank Ownership and Financial Performance: Mediation Effects of Indonesian Banking Capital Structure - Juniyan Gilang Cahyawan; Apriani Dorkas Rambu Atahau (Budapest International Research and Critics University, 2022)
This study aimed to examine the effect of the type of bank ownership on financial performance with capital structure as a mediating variable of the banking industry in Indonesia which is listed on the IDX, for the period 2018-2020. By using panel data regression analysis of 42 banks selected as samples, the results showed that capital structure could not mediate the effect of the type of bank ownership on financial performance. Likewise, there is no direct effect of the type of bank ownership on financial performance. This means that the type of bank ownership had no effect on bank's financial performance, either directly or indirectly. However, the type of bank ownership is proven to have an effect on the capital structure and the capital structure has a positive effect on the bank's financial performance. The implication of the research is the need for banks to manage their capital structure well to improve their financial performance.